Development of e-Worksheet Guided Inquiry-Oriented to Train Students' Critical Thinking Skills on Buffer Solution Material - Wahyuningtyas, Intan Nanda; Agustini, Rudiana (Department of Mathematics and Science Education, Faculty of Teacher Training and Education, University of Mataram. Jurnal Pijar MIPA colaborates with Perkumpulan Pendidik IPA Indonesia Wilayah Nusa Tenggara Barat, 2024)
Research titled Development of a Guided Inquiry-Oriented e-Worksheet to Train Students' Critical Thinking Skills on Buffer Solution Materials aims to produce e-worksheets to train critical thinking skills. This research is development research using the ADDIE model. The research design was a one-group pretest-posttest design. The feasibility of e-worksheet refers to three criteria: validity, practicality, and effectiveness. Validity consists of content validity and construct validity. Validity data is obtained from expert assessments through expert judgment. The results of the validity assessment stated that the e-worksheet developed had met the content and construct validity requirements in all aspects. Practicality data is obtained from students' physical activity observations, nonphysical activity observations, and student response questionnaires. Practicality and effectiveness data were obtained during the pilot test. Practicality data was obtained from observations of physical and nonphysical activities and student response questionnaires. The results of activity observations and learner response questionnaires show that the e-worksheet developed has met the practical criteria. Effectiveness data was obtained from the pretest and post-test results of students' critical thinking skills. The test results show that the developed e-worksheet has met the effective criteria.